Effects of Fatigue Induced by the Running-Based Anaerobic Sprint Test on the Performance in Execution Time and Decision-Making in Technical-Tactical Actions in Soccer (Passing and Driving) in a Laboratory Situation - Calle-Jaramillo, Guillermo Andrés; Gonzalez-Palacio, Enoc Valentin; Rojas Jaramillo, Andres; Gonzalez-Jurado, Jose Antonio (Physical Education Theory and Methodology, 2023)
Study purpose. The running-based anaerobic sprint test (RAST) has been developed to assess anaerobic power and fatigue levels using a repeated sprint protocol. The aim of this research was to study the effect of fatigue induced by RAST on performance in execution time (ET) and decision-making (DMA) in technical-tactical actions in soccer in a laboratory situation. Materials and methods. Quasi-experimental, longitudinal, pretest-posttest comparative study. Two groups of soccer players (n = 34) divided into a control group (n = 18) and an experimental group (n = 16) were evaluated twice at two different times. Results. Taking into account the p-value, effect size and statistical power, there are differences before and after RAST in the variables Total Index (TI) and ET, and not in DMA. On the other hand, the control group remained stable at both times. Conclusions. After the intervention, the experimental group showed a decrease in the figures of the ET and TI variables, but not in the DMA variable, in other words, the decisional time and motor time, components of the ET variable and essential at the time of rapid decision-making, increased in the posttest.